A METHOD FOR THE PREVENTION OF WOOD DECAY FROM NAIL PENETRATION. - DIAN-QING YANG
WOOD OFTEN FAILS IN STRUCTURES DUE TO DECAY AROUND NAIL FASTENINGS. NAILS MAY PENETRATE THE WOOD TREATED ZONE AND BRING FUNGAL SPORES INTO THE WOOD WHERE THE PRESERVATIVE HAS NOT REACHED.....
Sala de Colecciones abiertas
Inglés
R2290
FORE
Keywords: MADERA; ESTRUCTURAS DE MADERA; Artículos de revista